MUJAMIL QOMAR’S PERSPECTIVE ON RELIGIOUS MODERATION AND ITS IMPLEMENTATION FOR THE MUSLIM COMMUNITY IN INDONESIA - Mochammad Nginwanun Likullil Mahamid (Universitas Muhammadiyah Surakarta, 2022)
This article attempted to find out Mujamil Qomar's perspective on religious moderation and its implementation for the Muslim community in Indonesia, which was increasingly needed by the Indonesian people. This article aimed to provide an understanding to readers of the importance of instilling the spirit of religious moderation taught by experts in the field of Islamic education and thought. This article was written using a unit analysis study in a book entitled